การศึกษาแบบบูรณาการ กรณีศึกษา การจัดการเรียนการสอนอิสลามศึกษาแบบบูรณาการด้านกิจกรรม - มะแก้ว ประสพสุข (Al-HIKMAH Journal, 2021)
Abstract The objectives of this research on integrated Islamic education were to examine the history of integrated Islamic education, to explore integrated Islamic education policies, to investigate problems and obstacles in integrated Islamic education and to suggest the concept and developing method on integrated Islamic education. This study was considered both a documentary and a field research. Data were collected via primary data, secondary data as well as field data and followed by data analysis. Based on the preliminary study, the expected results of the research were as follows: 1) The schools understood the history of integrated Islamic education. 2) The schools comprehended integrated Islamic education policiesof the Islamic 3)The schools were aware of problems and obstacles in integrated Islamic education and could be used as guideline on the improvement and development of integrated education. 4) The schools got the concept and developing method on integrated Islamic education. Keywords : Teaching and learning, Islam education, integration, activities, educational model